The Biology and Function of Extracellular Vesicles in Cancer Development - Zhang, Xinyi; Liu, Dianfeng; Gao, Yongjian; Lin, Chao; An, Qingwu; Feng, Ye; Liu, Yangyang; Liu, Da; Luo, Haoming; Wang, Dongxu (Frontiers in Cell and Developmental Biology, 2021)
Extracellular vesicles (EVs) exert their biological functions by delivering proteins, metabolites, and nucleic acids to recipient cells. EVs play important roles in cancer development. The anti-tumor effect of EVs is by their cargos carrying proteins, metabolites, and nucleic acids to affect cell-to-cell communication. The characteristics of cell-to-cell communication can potentially be applied for the therapy of cancers, such as gastric cancer. In addition, EVs can be used as an effective cargos to deliver ncRNAs, peptides, and drugs, to target tumor tissues. In addition, EVs have the ability to regulate cell apoptosis, autophagy, proliferation, and migration of cancer cells. The ncRNA and peptides that were engaged with EVs were associated with cell signaling pathways in cancer development. This review focuses on the composition, cargo, function, mechanism, and application of EVs in cancers.